"LA FOTO NO ES BUENA": PHOTOGRAPHY, THE RESISTANT LOOK, AND THE FUTURITY OF "HOMOSEXUALIDADES LATINOAMERICANAS" IN PEDRO LEMEBEL'S "LA NOCHE DE LOS VISONES". - Bacsán, Gabriela (Chasqui (01458973), 2019)
The article focuses on that reference to the only photograph that exists of that party, which symbolizes the last meeting and celebration of locas from different backgrounds. It mentions that homonormativity functions as a political sedative as it establishes a notion of gay equality defined against the civil rights agenda and liberationism, as access to the institutions of domestic privacy, the free market, and patriotism.